Analisis Kedudukan Hukum Benda Menurut Kitab Undang-Undang Hukum Perdata - Qonita Nailah Basri; Adi Guna Wira Yudha; Cinta Nayla Gadinda Darsono; Afran Ghany; Muhammad Goefron; Helfira Citra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This research analyzes property law under the Civil Code, property rights and the principles that underlie them, the position of ownership rights as the most complete form of property rights, and pledge rights as one form of security rights. Property law is an important part of civil law because it regulates legal relations between legal subjects and the objects of rights. Property rights aim to create legal certainty, order, and protection for the parties in civil legal relations. This study uses a normative legal method with statute and conceptual approaches to analyze ownership and property rights. The results of the research show that the classification of objects greatly affects legal status and proof of ownership. Property rights are absolute in nature and are protected by the principle of publicity, the principle of totality, and the principle of legal certainty. Ownership rights form the basis for other property rights, with mechanisms for acquiring and losing rights regulated by law. In addition, pledge rights give priority to creditors and provide ease in the execution process, thus playing an important role in maintaining a balance of interests and legal certainty in civil legal relations.